Application of Administrative Ethics to Improve the Quality of the State Civil Apparatus - Arifah Rosmajudi Arifah Rosmajudi (Universitas Sultan Ageng Tirtayasa, 2022)
The government has implemented ethical obligations for state civil apparatus (ASN) clearly and unequivocally with the issuance of Government Regulation Number 42 of 2004 concerning the Guidance of Corps Spirit and Civil Servant Order. However, in practice, there are still ASN administrative ethics that are not in accordance with the provisions that have been set. The results of the researcher's initial observations show that the state civil apparatus in Cisalak District, Subang Regency, is considered to have not yet met the expectations of the community in terms of the quality of its human resources. This study aims to answer the question of the extent to which the application of administrative ethics can improve the quality of ASN in the Cisalak sub-district, Subang Regency. The study used qualitative methods with descriptive analysis. The results of the study indicate that the application of ethics in the administration of public administration, which is evident in the attitudes and behavior of the apparatus in carrying out their duties and responsibilities as a service, loyalty, sensitivity, equality, and courtesy in the state civil apparatus in Cisolok District, Subang Regency, has been running effectively.